Pengaruh Penambahan Asam Amino Metionin dengan Dosis yang Berbeda dalam Pakan Terhadap Pertumbuhan Ikan Nila Merah - Sumitro; Supasman Emu; La Ode Harsin (AquaMarine (Jurnal FPIK UNIDAYAN ), 2022)
The purpose of this study was to determine the effect of the dose of the amino acid methionine in the feed on the growth of red tilapia (Oreochromis niloticus). Tilapia measuring 5-7 cm were stocked in plastic drum containers with a diameter of 180 cm and a height of 60 cm with a density of 20 fish per container. The test feed is PIU (General Fish Feed) with 20-22% protein. The study used a completely randomized design (CRD) with 4 treatments and 3 replications. The research treatments were: 1) Methionine 0%, 2) Methionine 0.25%, 3) Methionine 0.50%, and 4) Methionine 0.75%. The results showed that the addition of methionine to a commercial feed of 0.75% showed the highest growth rate and good feed conversion compared to other treatments (P<0.05). The water quality measurement values obtained in this study are still within the range that supports the growth of tilapia.